Odpowiedź:
zad 13
a) (- 13 + 8) * (- 2) = ( - 5) * (- 2) = 10
b) (3 - 7) * ( 15 - 6) = (- 4) * 9 = - 36
c) (17 - 5) : ( - 3) = 12 : (- 3) = - 4
d) (- 5) * 2 * (- 7) = 35 * 2 = 70
e) (- 3) * (- 2) * ( - 4) = 6 * (- 4) = - 24
f) [(- 6) * ( - 5)] : (- 15) = 30 : (- 15) = - 30/15 = - 2
g) (- 5) * (- 2) + 6 * (- 3) = 10 + (- 18) = 10 - 18 = - 8
h) - 25 : (- 2 + 7) - 3 = - 25 : 5 - 3 = - 5 - 3 = - 8
i) [(- 8 + 2) : 3] * (8 - 15) =(- 6 : 3) * (- 7) = - 2 * (- 7) =14
j) (- 4 - 5 + 2)² = ( - 7)² = 49
k) (3 - 7 + 2)³ = (- 2)³ = - 8
l) (- 5 + 2)² - (- 2) * (- 5)² = (- 3)² - (- 2) * 25 = 9 - (- 50) = 9 + 50 = 59
zad 14
a)
(- 23 - 4)/( - 28 + 19) = (- 27)/(- 9) = 27/9 = 3
b)
(13 - 49)/(- 6) * 5 = (- 36)/(- 6) * 5 = 36/6 * 5 = 6 * 5 = 30
c)
[25 - (- 3)/[- 2 * (- 15 + 8) = (25 + 3)/[- 2 * (- 7)] = 28/14 = 2
d)
[(- 5)² - (- 1)²]/[(- 2)³ + 2] = (25 - 1)/(- 8 + 2) = 24/(- 6) = - 24/6 = - 4